Green Carbon Part 1 The role of natural forests in carbon storage - Mackey, Brendan (ANU Press, 2008)
The colour of carbon matters. Green carbon is the carbon stored in the plants and soil of natural ecosystems and is a vital part of the global carbon cycle. This report is the first in a series that examines the role of natural forests in the storage of carbon, the impacts of human land use activities, and the implications for climate change policy nationally and internationally. REDD ("reducing emissions from deforestation and degradation") is now part of the agenda for the "Bali Action Plan" being debated in the lead-up to the Copenhagen climate change conference in 2009. Currently, international rules are blind to the colour of carbon so that the green carbon in natural forests is not recognised, resulting in perverse outcomes including ongoing deforestation and forest degradation, and the conversion of extensive areas of land to industrial plantations. This report examines REDD policy from a green carbon scientific perspective. Subsequent reports will focus on issues concerning the carbon sequestration potential of commercially logged natural forests, methods for monitoring REDD, and the long term implications of forest policy and management for the global carbon cycle and climate change.